(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The composites of poly(lactic acid) (PLA) with untreated or alkali treated (A-) or silane-coupling treated (SC-) flax noil fibers (flax) were prepared by non-woven method and hot pressing technology. The biodegradability of the composites was evaluated by activated soil-burial test. The presence of untreated flax or A-flax or SC-flax led to the acceleration of weight loss due to preferential degradation of flax, which was demonstrated in the SEM micrographs and FTIR spectra. Rates of weight loss decreased in the order flax/PLA (24.0%/35days) > A-flax/PLA (20.6%/35days) > SC-flax/PLA (17.8%/35days) and also decreased with interface shear strengths of the composites. The weight loss of PLA and flax after 35 days was 4% and 52.5% respectively.